2009
DOI: 10.1111/j.1600-0722.2009.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoridated carbamide peroxide gels on enamel microtensile bond strength

Abstract: The aim of this study was to examine the resin bond strength on enamel treated with different fluoridated bleaching agents. Forty-eight bovine incisors were divided into four groups to receive bleaching treatments, over a 14-d period, as follows: no treatment; 10% carbamide peroxide (CP) bleaching; 10% CP containing 0.11% fluoride; and 10% CP containing 0.37% fluoride. Immediately, and 7 and 14 d after bleaching, the enamel surfaces were respectively bonded with composite and sectioned to create resin-enamel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
13
0
3
Order By: Relevance
“…According to the authors, the positive outcome of F -addition to bleaching agents may assist subsequent restorative treatment by inhibiting enamel demineralization. 21 Failure mode patterns of CP-treated interfaces demonstrated predominance (35 to 45%) of cohesive failure in the enamel for both the bleaching agents used in this study. The cohesive failures confirm the hypothesis that bleaching may promote enamel structural changes, thus initializing fracture during debonding at the enamel rather than at the adhesive-bonded interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, the positive outcome of F -addition to bleaching agents may assist subsequent restorative treatment by inhibiting enamel demineralization. 21 Failure mode patterns of CP-treated interfaces demonstrated predominance (35 to 45%) of cohesive failure in the enamel for both the bleaching agents used in this study. The cohesive failures confirm the hypothesis that bleaching may promote enamel structural changes, thus initializing fracture during debonding at the enamel rather than at the adhesive-bonded interface.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel demineralization promoted by CP might have helped to lower the bond strength. Chuang et al 21 observed that 10% CP containing high F -concentrations (0.37%) was able to maintain µTBS as effectively as unbleached enamel. The authors observed that non-fluoridated and 0.11% fluoridated CP agents exhibited lower µTBS immediately after bleaching, which is in accordance with our findings, but their reported values were recovered after 7 and 14 days of storage.…”
Section: Discussionmentioning
confidence: 99%
“…The Fluoride use in the composition of bleaching agent was also studied order to increase the bond strength after bleaching, which was not found in the research conducted [26].…”
Section: Mechanisms For Immediate Adhesion After-bleachingmentioning
confidence: 99%
“…De acordo com a literatura, dentre os testes que avaliam o comportamento das restaurações adesivas em esmalte clareado, destacam-se o teste de cisalhamento (KIMYAI;VALIZADEH 2006;KOGA;BORGES, 2006;MURAGUCHI et al 2007;GÖKÇE et al 2008;TÜRKÜN;ARICI, 2008;SASAKI;FLÓRIO;BASTING, 2009;KHOROUSHI;AGHELINEJAD, 2011) e de microtração (LAI et al, 2002ARCARI et al 2007;CHUANG et al, 2009;BARCELLOS et al, 2010;LAGO, DE FREITAS;NETTO, 2011;ROCHA GOMES TORRES et al, 2012) . Na presente pesquisa, foi utilizado o teste de microtração levando em consideração que os valores obtidos podem ser correlacionados mais precisamente aos achados clínicos (HEINTZE, 2013).…”
Section: Tipos De Fraturaunclassified